Aborto en bovinos por consumo de pino : análisis toxológico de coníferas en la Patagonia Argentina - Martinez, Agustin; Gardner, Dale R.; Caballe, Gonzalo; Diaz, Eugenio; Apostolo, Romina Maria; Mikuc, Juan Pablo; Robles, Carlos Alejandro (Edición del Autor, 2018)
Poster